2014
DOI: 10.1007/s10457-014-9691-8
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of cocoa agroforestry systems to family income and domestic consumption: looking toward intensification

Abstract: While the potential of agroforestry products to contribute to rural livelihoods is well-recognized, the quantification of their yields, incomes, and value for domestic consumption (VDC) and knowledge about their relationships with biodiversity are still scarce. This information is crucial for choosing the best strategy for growing cocoa in tropical landscapes while conserving biodiversity and enhancing ecosystem services. We analyzed the contribution of cocoa agroforestry farming to the incomes and domestic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
74
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(101 citation statements)
references
References 54 publications
8
74
0
8
Order By: Relevance
“…3b). Thus, our results show that agroforestry systems not only support farmers' livelihood because of the higher diversification of crops for self-consumption, as has been widely reported (Cerda et al 2014), but also they have higher return on labor than the full-sun monocultures.…”
Section: Return On Laborsupporting
confidence: 76%
See 3 more Smart Citations
“…3b). Thus, our results show that agroforestry systems not only support farmers' livelihood because of the higher diversification of crops for self-consumption, as has been widely reported (Cerda et al 2014), but also they have higher return on labor than the full-sun monocultures.…”
Section: Return On Laborsupporting
confidence: 76%
“…However, cacao production under organic farming is still very low, i.e., approximately 2.3% of the global production area (Willer and Lernoud 2015). Several studies have already demonstrated that agroforestry systems can improve farmers' livelihoods due to self-consumption of by-crops, such as bananas, oranges, and peach palm, among others (Cerda et al 2014). However, when assessing cacao production systems, most studies focus on cacao yields without quantitatively assessing the economic returns of by-crops (Cerda et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Home gardens can be a form of agroforestry (Kehlenbeck et al 2007), and may be an important pathway through which agroforestry could contribute to nutrition . A recent paper by Cerda et al (2014) using yield and crop use information for cacao agroforestry systems in multiple Central American countries concluded that diversity in canopy trees is associated with increased fruit available for home consumption. However, to date, no published studies have tested the relationship between agroforestry (other than home-gardens) and dietary intake.…”
Section: Forests and Tree-based Systemsmentioning
confidence: 99%